Associations of GP practice characteristics with the rate of ambulatory care sensitive conditions in people living with dementia in England: an ecological analysis of routine data - Eyles, Emily (BMC Health Serv Res, 2021)
BACKGROUND: Hospital admissions for Ambulatory Care Sensitive Conditions (ACSCs) are potentially avoidable. Dementia is one of the leading chronic conditions in terms of variability in ACSC admissions by general practice, as well as accounting for around a third of UK emergency admissions. METHODS: Using Bayesian multilevel linear regression models, we examined the ecological association of organizational characteristics of general practices (ACSC n=7076, non-ACSC n=7046 units) and Clinical Commissioning Groups (CCG n=212 units) in relation to ACSC and non-ACSC admissions for people with dementia in England. RESULTS: The rate of hospital admissions are variable between GP practices, with deprivation and being admitted from home as risk factors for admission for ACSC and non-ACSC admissions. The budget allocated by the CCG to mental health shows diverging effects for ACSC versus non-ACSC admissions, so it is likely there is some geographic variation. CONCLUSIONS: A variety of factors that could explain avoidable admissions for PWD at the practice level were examined; most were equally predictive for avoidable and non-avoidable admissions. However, a high amount of variation found at the practice level, in conjunction with the diverging effects of the CCG mental health budget, implies that guidance may be applied inconsistently, or local services may have differences in referral criteria. This indicates there is potential scope for improvement. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at (10.1186/s12913-021-06634-7).